Rethinking mission, missions and money: A focus on the Baptist Church in Central Africa - Kighoma, Eraston Kambale (HTS teologiese studies, 2019)
The African church has the most growing figures compared to the west and yet it contributes the least to world missions. This article analyses the issue of disparity in funding mission practices between the African church and its mother church, the Western church. It then explores reasons behind the African church’s struggles to support missions and identifies opportunities for world missions to which the eastern Congolese church is exposed. A critical analysis of different arguments and reports from different authors was used to draw the main conclusions and, therefore, identify the central reason of the disparity and provide recommendations for the two churches. The paper suggests how scholars and the church should rethink mission, missions and money in Eastern Congo.